Kinetic Model For Growth And Influence Of pH ON THE Growth Of Halochlorella Rubescens In A Fabricated Photobioreactor - Jais, Nur Izatul Anis Muhammad (Universiti Sains Malaysia, 2020)
For years, Chlorella sp, have been proven to be one of the candidates in producing abundant amounts of algal biomass. In this study, the fabrication of a new reactor was done and performance of Halochlorella rubescens, microalgae under genus Chlorella sp. in producing high cell mass was studied.